Adsorption of Acrylic Acid from Process Water Using Activated Carbon Adsorption Equilibrium Study - Sumathi, S.; Anwaruddin, Hisyam; K., Ramesh (2014)
Process water from petrochemical industry contains a lot of chemical components and one of the prominent components is acrylic acid (AA). High exposure to AA could lead severe problems to the environment and human. Thus, in this study the capability of removing process water AA by adsorption using coconut based activated carbon (CAC) was tested. The effect of contact time and adsorbent dosage was studied. Other operating conditions were fixed, i.e. concentration of AA (40g/1), pH (3.0), shaking speed (150rpm) and temperature (30±1)°C. The removal capacity was determined using HPLC. The optimum weight and contact time of the adsorption process was 500g/L and 100 min respectively. The best model of equilibrium adsorption was presented by Langmuir isotherm model with R2 of 0.9427. Adsorption process of acrylic acid by activated carbon was favorable with the value of R is 0.125 (0<R< 1) and 1/n is less than 1. Adsorption of AA by CAC was governed by monolayer localized physical adsorption on a homogenous surface. The adsorption capacity of CAC for AA is 89.9mg/l.